2005
DOI: 10.1186/1477-7827-3-11
|View full text |Cite
|
Sign up to set email alerts
|

Mitochondrial 3 beta-hydroxysteroid dehydrogenase (HSD) is essential for the synthesis of progesterone by corpora lutea: An hypothesis

Abstract: In mouse ovaries, the enzyme 3 beta-hydroxysteroid dehydrogenase (HSD) is distributed between microsomes and mitochondria. Throughout the follicular phase of the estrous cycle, the HSD activity in microsomes is predominant; whereas, after LH stimulation, HSD activity during the luteal phase is highest in the mitochondria. The current study examined whether or not LH stimulation always results in an increase in mitochondrial HSD activity. This was accomplished by measuring the HSD activity in microsomal and mit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
11
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 32 publications
(12 citation statements)
references
References 81 publications
1
11
0
Order By: Relevance
“…The HSD3B2‐GFP fluorescence illuminated rings around LipidTox stained spheres and co‐localized with the LD marker protein Plin2‐DsRed or Plin1‐mCherry, and showed similar localization profile (Figure ; Figure S3–S6, Supporting Information). The HSD3B2‐GFP was also co‐localized with ER marker KDEL‐Red when it was not on LDs in all cell lines, and in some cell lines HSD3B2‐GFP was also observed to co‐localize with mitochondrial markers, and Mito‐DsRed (Figure ; Figure S3–S6, Supporting Information), which is consistent with previous findings . There was no obvious LD localization of HSD3B2‐GFP in Hela cells under normal growth conditions where only a few small LDs are found.…”
Section: Resultssupporting
confidence: 90%
“…The HSD3B2‐GFP fluorescence illuminated rings around LipidTox stained spheres and co‐localized with the LD marker protein Plin2‐DsRed or Plin1‐mCherry, and showed similar localization profile (Figure ; Figure S3–S6, Supporting Information). The HSD3B2‐GFP was also co‐localized with ER marker KDEL‐Red when it was not on LDs in all cell lines, and in some cell lines HSD3B2‐GFP was also observed to co‐localize with mitochondrial markers, and Mito‐DsRed (Figure ; Figure S3–S6, Supporting Information), which is consistent with previous findings . There was no obvious LD localization of HSD3B2‐GFP in Hela cells under normal growth conditions where only a few small LDs are found.…”
Section: Resultssupporting
confidence: 90%
“…Consequently, unlike many metabolic pathways (e.g., glycolysis, citric acid cycle, fatty acid synthesis), the committed step in steroidogenesis is not an enzymatic reaction (i.e., the P450sccmediated conversion of cholesterol to pregnenolone, which was previously thought to be one), but rather, cholesterol transport to the mitochondria that is mediated by the StAR protein [2]. In addition to P450scc, 11-hydroxysteroid dehydrogenase and aldosterone synthase in adrenocortical cells localize to the mitochondrial IMM, and 3β-hydroxysteroid dehydrogenase has been reported to be present in the mitochondria [9]. In fact, 3β-HSD was first isolated from the mitochondria [10].…”
Section: Steroidogenic Cells and Steroidogenic Mitochondriamentioning
confidence: 98%
“…The NAD(H) and the NADP(H) pools are compartmentalized in cells, but it has been demonstrated that they are connected by the nicotinamide nucleotide transhydrogenase (NNT; Fisher-Wellman et al, 2015 ). In addition, the 3βHSD utilizes NAD as a co-factor (Chapman et al, 2005 ). Finally, as hydroxysteroid dehydrogenases enzymes use the nicotinamide cofactors to interconvert steroid hormones, and as their activities depend mainly on cofactors abundance, levels of steroids may be modulated by the levels of these cofactors and consequently by the redox state of the cells (Agarwal and Auchus, 2005 ).…”
Section: The Decline Of Brain Steroid Levels During Agingmentioning
confidence: 99%